Perbedaan Nilai Rasio Neutrofil Terhadap Limfosit Pada Pasien Tuberkulosis Dewasa Sebelum dan Setelah Terapi Fase Intensif di RS Atma Jaya - Cahyadi, Alius; Steffanus, Mario (Majalah Kedokteran Indonesia, 2018)
Introduction: Tuberculosis (TB) is an important health problem in developing countries. This infection results neutrophilia and lymphopenia. The neutrophil to lymphocyte ratio (NLR) is an easy, inexpensive, and sensitive examination. The NLR result in tuberculosis patients showed higher compare to normal population, with cut off greater than 2.16. The aim of this study was to know the difference of NLR result in adult TB patients before and after the intensive phase treatment. Methods: We collected all new cases adult TB patients who came to out-patient department in Atma Jaya Hospital, without any HIV infection, chronic kidney disease, diabetes mellitus, chronic obstructive pulmonary disease, and bacterial pneumonia. Baseline characteristic, leukocyte count, neutrophil and lymphocyte count, also NLR were collected before and after intensive phase treatment, then were analyzed using SPSS. Results: There were 44 participants included in this study, 23 (52.3%) of them were male, with median age were 37 years old. Eighty eight percent of the subject had pulmonary tuberculosis. The NLR result before treatment (2.77) was higher compare with the NLR result (2) after intensive phase treatment (p less than 0.001). Conclusion: There was a statistically significant decrease in NLR result after intensive phase treatment of adult TB patients.